2016
DOI: 10.15287/afr.2016.574
|View full text |Cite
|
Sign up to set email alerts
|

Inventory-based estimation of forest biomass in Shitai County, China: A comparison of five methods

Abstract: Abstract. Several comparative studies have reported that there can be great discrepancies between different methods used to estimate forest biomass. With the development of carbon markets, an accurate estimation at the regional scale (i.e. county level) is becoming increasingly important for local government. In this study, we applied five methodologies [continuous biomass expansion factor (CBEF) approach, mean biomass density (MB) approach, mean biomass expansion factor (MBEF) approach, national continuous bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…The basin has complicated topographic features, and is surrounded by mountains and hills in the eastern, southern, and western parts of the basin and dominated by flat terrains in the central and northern parts. The basin has a humid mid-subtropical monsoon climate with distinct seasonality [53,54]. The mean annual temperature is approximately 17.5 • C with a mean annual precipitation of 1400 mm.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The basin has complicated topographic features, and is surrounded by mountains and hills in the eastern, southern, and western parts of the basin and dominated by flat terrains in the central and northern parts. The basin has a humid mid-subtropical monsoon climate with distinct seasonality [53,54]. The mean annual temperature is approximately 17.5 • C with a mean annual precipitation of 1400 mm.…”
Section: Study Areamentioning
confidence: 99%
“…In this study, several allometric equations were used to estimate the values of AGB of trees by species; however, the uncertainty from the used allometric equations was unknown. In addition, Tang et al [54] demonstrated that selecting spatial extrapolation methods is also vital for estimation and mapping of forest ecosystem AGB. In this study, three kinds of methods were compared using the same dataset and spectral variables.…”
Section: Uncertainty Analysis Of Forest Biomassmentioning
confidence: 99%
“…Deforestation, forest fires, and natural regeneration can all affect the applicability of the volume formula [ 27 ]. It is therefore crucial for the forest survey program in Wangyedian Forest Farm to obtain updated forest resource data annually while checking and calibrating volume equations periodically [ 9 , 27 ]. This would help to substantially reduce the error of the plot level GSV estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate estimation of the GSV, therefore, plays an important role in both forest resource management and the monitoring of ecosystem dynamics [ 4 , 5 , 6 ]. Compared with traditional field surveys, remote sensing technology allows for a more efficient approach to the monitoring and management of forest resources in real-time [ 7 , 8 , 9 ]. However, the accuracy of GSV estimation using remotely sensed data is determined together by data sources, feature variable selection methods, and estimation models.…”
Section: Introductionmentioning
confidence: 99%
“…The FMI plays a very important role in improving provincial forest planning, efficient management, and policy decision-making. Therefore, FMI data are widely used in many types of research, including forest health assessment and land cover change monitoring [54,55]. The FMI data of Ganzhou and Kangbao collected in 2017 and 2013, respectively, show six land cover types: unused land, water, forest, farmland, building, and grassland.…”
Section: Sampling Design and Leaf Area Index Measurementmentioning
confidence: 99%